Spiritual Intelligence and Emotional Intelligence on the Spiritual Leadership Style of Government Structural Officials - Khairil Fauzan K.; Arif Fachrian; Eva Yulina; Tengku Nuranasmita (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
There is a phenomenon of structural officials of the Government of Aceh Tamiang Regency, Aceh Province who have not fulfilled their capacity as leaders, because there are still actions that deviate and do not follow existing procedures. The aim of the research was to determine the relationship between spiritual intelligence and emotional intelligence with the spiritual leadership style of the structural officials of the Government of Aceh Tamiang District, Aceh Province. The population of 109 officials and a sample of 52 people was obtained from the slovin formula and using a lottery random sampling technique. The method used is instrument test, validity and reliability test, classical assumption test, heteroscedasticity test, and linearity test. The research results obtained are that there is a positive and significant relationship between spiritual intelligence and spiritual leadership style. There is a positive and significant relationship between emotional intelligence and spiritual leadership style. Together there is a relationship between spiritual intelligence and emotional intelligence with spiritual leadership style. Thus, leaders must be able to improve their leadership development in terms of spiritual intelligence and emotional intelligence. These two things are very important in order to increase the spiritual leadership style of the leader. So the hypothesis in this study can be accepted theoretically. It is suggested that officials can develop the ability of spiritual intelligence and emotional intelligence through various ways such as: participating in ESQ training, participating in various spiritual education so that it can be used as a basis for conducting coaching.Adanya fenomena pejabat struktural Pemerintah Kabupaten Aceh Tamiang Provinsi Aceh yang belum memenuhi kapasitasnya sebagai pemimpin, karena masih adanya tindakan yang melenceng dan tidak mengikuti prosedur yang ada. Tujuan penelitian dilakukan untuk mengetahui hubungan kecerdasan spiritual dan kecerdasan emosional dengan gaya kepemimpinan spiritual pejabat struktural Pemerintah Kabupaten Aceh Tamiang Provinsi Aceh. Populasi sebanyak 109 orang pejabat dan sampel 52 orang diperoleh dari rumus slovin dan menggunakan teknik random sampling secara lotere. Metode yang digunakan adalah uji instrumen, uji validitas dan reliabilitas, uji asumsi klasik, uji heteroskedastisitas, dan uji linearitas. Hasil penelitian yang diperoleh adalah ada hubungan positif dan signifikan antara kecerdasan spiritual dengan gaya kepemimpinan spiritual. Ada hubungan positif dan signifikan antara kecerdasan emosional dengan gaya kepemimpinan spiritual. Secara bersama ada hubungan kecerdasan spiritual dan kecerdasan emosional dengan gaya kepemimpinan spiritual. Dengan demikian pemimpin harus mampu meningkatkan pengembangan kepemimpinannya secara kecerdasan spiritualitas maupun kecerdasan emosional. Kedua hal ini sangat penting guna peningkatan gaya kepemimpinan spiritual pada pemimpin. Sehingga hipotesis dalam penelitian ini dapat diterima secara teoritis. Disarankan agar pejabat dapat mengembangkan kemampuan kecerdasan spiritual dan kecerdasan emosional melalui berbagai cara seperti: mengikuti training ESQ, meengikuti berbagai pendidikan spiritual sehingga dapat dijadikan sebagai dasar untuk melakukan pembinaan.